Surface Roughness Determination in Turning of Cylindrical Surfaces - Felho, Csaba; Kundrak, Janos (Manufacturing Technology Journal, 2009)
The topic of the article is the determination of theoretical values of surface roughness on cylindrical surfaces machined by turning. For the calculation of the values of main roughness parameters (Rmax, Rz, Ra) a general mathematical model was developed, and a computer software based on this model has also developed. In the article this model and the software based on it gets introduced briefly, as the determination of connections between calculated theoretical values and measured data obtained through experiments.
Keywords: surface roughness; theoretical roughness